Into the wild : escaped farmed rainbow trout show a dispersal-associated diet shift towards natural prey - Nabaes Jodar, Diego Nicolás (2019)
The feeding ecology of farmed fish escapees has seldom been assessed, although they are one of aquaculture’s main environmental impacts. Here we tested if the diet of Oncorhynchus mykiss rainbow trout escapees was affected by their dispersal from farms in a reservoir in Argentine Patagonia by combining stomach content and stable isotope data, and compared their spatial patternswith those of caged and wild (previously naturalized) conspecifics. Our results reveal a shift in the stomach content and d13C values of escapees, reflecting a farm (pellets) to wild (mainly Daphnia sp.) diet transition associated to dispersal from farms. The d13C signal of escapees sampled within the farming area was close to that of caged fish, whereas the d13C of escapees captured far from it was indistinguishable from that of wild rainbow trout. Furthermore, escapee dispersal from farms was associated with a transition from indiscriminate surface feeding (on indigestible floating items) typical of caged fish to preying heavily on Daphnia sp. In contrast, wild fish diet was homogeneous across all sites. Farm escapees gradually acquiring the feeding behavior of their wild conspecifics as they disperse from the farms may promote competition for food and space, and increase their chances for survival in the wild.